Returns to type or tenure? - Roland A. Amann; Tobias J. Klein (Institute for the Study of Labor (IZA), 2007)
We analyze the joint determination of wage levels, wage growth and firm tenure. Our analysis is built on estimating a reduced form for tenure, a structural wage level equation and a structural wage growth equation. We disentangle returns to a latent type variable from estimates of general returns to tenure and wage gains from job changes. This type is related to unobservable match quality that is allowed to vary over time and to be correlated with the returns to tenure. The obtained results for Germany indicate that the type plays a crucial role in the remuneration of employees. Those types who change jobs more often obtain steeper wage profiles but earn less on average.
urn:nbn:de:101:1-2008040218
Keywords: 330; Betriebszugehörigkeit; Lohnstruktur; Arbeitsmobilität; Theorie; Deutschland